ANALISIS PENERAPAN APLIKASI SISKEUDES SEBAGAI ALAT BANTU DALAM PENGELOLAAN KEUANGAN PADA DESA CIKEMBAR - Zaman, Faris Qomarrul (Universitas Muhammadiyah Tangerang, 2023)
The purpose of this study was to find out how to implement the SISKEUDES application in Cikembar Village, Cikembar District, Sukabumi Regency from the many obstacles faced such as inadequate human resources in quality and quantity and to find out whether there was an obstacle in terms of the Siskeudes application itself so that it hindered the implementation of the SISKEUDES application. village financial management. This study uses a qualitative method with a descriptive approachKeywords: pengelolaan keuangan desa, aplikasi siskeudes